Plan estratégico para el mejoramiento de los servicios educativos en el área técnica de la unidad educativa 16 de Mayo, cantón Quinsaloma, periodo 2014 -2017. - Macías Bajaña, Karem Johanna (2015)
The College May 16 of Quinsaloma canton, is a public educational institution that provides knowledge, education and wisdom to each youth that comprise it. At present the institution provides the opportunity to train in technical careers such as: agricultural holdings, computer applications and management accounting. In order to improve the educational quality of the institution the following research entitled "STRATEGIC PLAN FOR THE IMPROVEMENT OF EDUCATIONAL SERVICES IN THE AREA OF TECHNICAL EDUCATION UNIT MAY 16, Quinsaloma Canton, 2014-2017" is presented. Whereby through a SWOT analysis the current situation to analyze the internal and external environment, each of the specialties of the technical area of the school, besides designing the organizational structure of the entity was made stipulating the organization was determined the information gathered to determine the background, history, mission, vision, corporate objectives, policies, values, functional organization and philosophy, determining all possible strategies that involve a change of continuous improvement in teamwork to strengthen institutional development and educational, giving as a result a quality education that today's young people deserve in regard to technical careers that offer the "Education Unit May 16", for it five operational plans developed, of which based on strategic objectives, among which are mentioned; Manage increasing technological infrastructure; Manage the donation of land for specialty practices agriculture; Perform updates in pedagogical innovation, to have teachers of academic excellence; Conduct training to students in the technical areas of accounting, computer and agricultural; Motivate students in undertaking activities that contribute to society; all aims to solve those needs facing students of the institution.